2017
DOI: 10.3390/ijerph14121526
|View full text |Cite
|
Sign up to set email alerts
|

Pets, Purity and Pollution: Why Conventional Models of Disease Transmission Do Not Work for Pet Rat Owners

Abstract: In the United Kingdom, following the emergence of Seoul hantavirus in pet rat owners in 2012, public health authorities tried to communicate the risk of this zoonotic disease, but had limited success. To explore this lack of engagement with health advice, we conducted in-depth, semi-structured interviews with pet rat owners and analysed them using a grounded theory approach. The findings from these interviews suggest that rat owners construct their pets as different from wild rats, and by elevating the rat to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Control of SEOV in the Netherlands would be complicated because many rat breeders and owners are not registered, and it is not yet known what measures could be effective to reduce transmission of the virus among rats. To prevent new human SEOV cases, we therefore suggest improving public education on SEOV [ 31 ]. From our questionnaires, it became clear that improvements in hygiene measures are possible; especially washing hands after contact with the rats and wetting of the bedding was practiced by only a limited number of pet rat and rattery owners.…”
Section: Discussionmentioning
confidence: 99%
“…Control of SEOV in the Netherlands would be complicated because many rat breeders and owners are not registered, and it is not yet known what measures could be effective to reduce transmission of the virus among rats. To prevent new human SEOV cases, we therefore suggest improving public education on SEOV [ 31 ]. From our questionnaires, it became clear that improvements in hygiene measures are possible; especially washing hands after contact with the rats and wetting of the bedding was practiced by only a limited number of pet rat and rattery owners.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the patient and her daughter reported kissing the rats and housing them in bedrooms. Owners might not follow public health advice on preventive measures such as avoiding kissing or holding small mammals near the face and keeping rodents out of sleeping and eating areas; public health messaging should be tailored to address the specific health beliefs of this community ( 14 ). Although the patient in this study agreed to the proposed euthanasia of her rats, the breeder preemptively removed them from the property and refused to cooperate further, mirroring the behavior of breeders in other outbreaks ( 10 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…"animal model", aversion could very well explain why, since the beginning of the twentieth century, rodents, and not dogs, have become a primary "animal model" for invasive research. Narratives about animals have significant power to structure human action (see also Robin et al 2017). The way perception affects our moral psychology often remains hidden in the background, and because these "are not always introspectively accessible, even a moral action can take place against the background of unconscious, non-virtuous tendencies of cognitive response" (Westerhoff 2017, 299).…”
Section: How Fear and Disgust Impair Moral Judgmentmentioning
confidence: 99%